2020
DOI: 10.1039/d0ra00053a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of WO3 and SiO2 doping on CeO2–TiO2 catalysts for selective catalytic reduction of NO with ammonia

Abstract: A series of CeO2–WO3/TiO2–SiO2 catalysts were prepared for SCR of NOx with NH3, and the effect of WO3 and SiO2 doping on the activity and stability of the catalysts were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Fan et al. found that SiO 2 addition can significantly enhance higher hydrothermal stability of CeO 2 /TiO 2 −SiO 2 especially between 550 and 600 °C [49c] …”
Section: Methods In Improving the Catalytic Activity Of Ceo2−tio2 Catalystmentioning
confidence: 99%
“…Fan et al. found that SiO 2 addition can significantly enhance higher hydrothermal stability of CeO 2 /TiO 2 −SiO 2 especially between 550 and 600 °C [49c] …”
Section: Methods In Improving the Catalytic Activity Of Ceo2−tio2 Catalystmentioning
confidence: 99%
“…The highly dispersed WO3 enhanced the Ce-O-W reaction and Ce-O-Ti reaction, and consequently improved the performance of the NH3-SCR catalysts. Besides, the addition of WO3 improved the thermal stability of the catalysts at 550-600 °C [89], and a large cerium oxide phase and more TiO2 crystal formation can be avoided in the catalytic reaction process [90]. Eventually, from the reported work on the Ce-Mn/TiO 2 catalyst, it is not difficult to find that the rich variable valence states of Mn show excellent NH 3 -SCR activity at low temperature.…”
Section: Ce-w/tio2 Catalystmentioning
confidence: 99%
“…The diffraction peak at 28.28°33.08°47.48°could be attributed to the (111), ( 200), (220) crystal plane of CeO 2 (PDF card: 89-8436), this indicated that a new CeO 2 crystal phase was formed. [37] This may be the reason that the catalytic activity no longer changed obviously with the cerium content exceeded 15 % in mainly temperature ranges. The CeO 2 /TiO 2 catalyst showed a strong TiO 2 diffraction peak and a slight CeO 2 diffraction peak, which indicated that a small amount of tungsten was helpful for the dispersion of Cerium (Figure 2b).…”
Section: Structure Analysismentioning
confidence: 99%